Perception of Cooperative Financial Reporting Accountability for Sustainable Welfare - Purnamawati, I Gusti Ayu (Jurnal Riset Akuntansi dan Keuangan, 2020)
This study aims to determine how perceptions of Cooperatives in Buleleng District towards financial reporting accountability to realize prosperity. This research uses quantitative and qualitative descriptive approaches. The type of data used is primary data and secondary data. Collecting data using survey methods, distributing closed questionnaires to respondents who became the study sample, and conducting interviews with some of the respondents, as many as 174 questionnaires, 87 questionnaires at the implementation level, and 87 questionnaires for the perception of cooperative actors. Likert scale 1-5 was used for questionnaires. The results showed that the financial accountability implementation through Financial Accounting Standards for Entities without Public Accountability (SAK ETAP/FAS-EWPA) in cooperatives in the Buleleng sub-district that most cooperatives were sufficient to apply but only on certain principles. The perception of cooperative actors towards the implementation of SAK ETAP shows a good category, the evaluation results are confirmed through in-depth interviews.